Refractómetro de cubeta de sección cuadrada - Duque D., M.F.; Gómez P., S.; Pinilla C., C.C.; Duque D., C.A. (Revista Mexicana de Física E, 2006)
In this paper a simple and accurate method to measure refraction index for liquid substances is described. It is based on a cubic edge refractometer, where probes for several liquids such as common Water and Ethylic Alcohol were done. Also, a measure of refraction index for a Water-Ethylic Alcohol mixture at different concentration levels was carried out. We show results for all those experiments together with a detailed description of the refractometer operation. Finally a mathematical relation between refraction index and concentration level is given by the Water-Ethylic Alcohol experiment.